2018
DOI: 10.1371/journal.pone.0190447
|View full text |Cite
|
Sign up to set email alerts
|

Network-based co-expression analysis for exploring the potential diagnostic biomarkers of metastatic melanoma

Abstract: Metastatic melanoma is an aggressive skin cancer and is one of the global malignancies with high mortality and morbidity. It is essential to identify and verify diagnostic biomarkers of early metastatic melanoma. Previous studies have systematically assessed protein biomarkers and mRNA-based expression characteristics. However, molecular markers for the early diagnosis of metastatic melanoma have not been identified. To explore potential regulatory targets, we have analyzed the gene microarray expression profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 45 publications
1
43
0
Order By: Relevance
“…A third PPI of interest is indicated by the generated String network between Argonaute 3 and SP1, in the presence of miR‐150‐5p, supported experimental data, co‐expression data, data from curated databases, and textmining. SP1 has been previously identified as a core transcriptional regulator in metastatic melanoma, associated with regulation of 24 differentially expressed hub genes involved in the immune response, tumor cell development, and tumorigenesis in melanoma . This suggests a potential regulatory role for miR‐150‐5p on differentially expressed genes in the setting of metastatic melanoma through interaction with SP1 via Argonaute 3.…”
Section: Discussionmentioning
confidence: 95%
“…A third PPI of interest is indicated by the generated String network between Argonaute 3 and SP1, in the presence of miR‐150‐5p, supported experimental data, co‐expression data, data from curated databases, and textmining. SP1 has been previously identified as a core transcriptional regulator in metastatic melanoma, associated with regulation of 24 differentially expressed hub genes involved in the immune response, tumor cell development, and tumorigenesis in melanoma . This suggests a potential regulatory role for miR‐150‐5p on differentially expressed genes in the setting of metastatic melanoma through interaction with SP1 via Argonaute 3.…”
Section: Discussionmentioning
confidence: 95%
“…Melanoma is one of the most common skin malignancies, and poor patient prognosis is signi cantly associated with its high metastatic capacity [44]. Although many novel diagnostic techniques and molecular biomarkers have been discovered in recent years, they have not su ciently improved early diagnosis and prognosis of SKCM [11]. Therefore, it is imperative to identify SKCM prognosis-related molecules and the exact mechanism of cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, therapeutic effectiveness remains limited due to lack of knowledge regarding the intricate mechanism underlying SKCM metastasis. In recent years, many studies have focused on identifying potential biomarkers for metastatic melanoma [11,12]. Unfortunately, these developments have been inadequate for improving early diagnosis and prognosis of SKCM.…”
Section: Introductionmentioning
confidence: 99%
“…P2RY10 belongs to the family of G -protein -coupled receptors, which are activated by adenosine and uridine [63]. Wang et al found that P2RY10 was potentially involved in the immune response and the development of sarcomas [64]. RASL3, a novel member of the RasGAP Rasal family, is predominantly expressed by T cells [65,66], and RasGAP activity stimulates ERK phosphorylation.…”
Section: Discussionmentioning
confidence: 99%